2021
DOI: 10.1002/adom.202101905
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Zn‐Based Organic‐Inorganic Hybrid Ferroelectrics with Large Polarization and Luminescence

Abstract: Multi‐functionalized lead‐free organic‐inorganic hybrid ferroelectrics have recently realized diverse applications especially for optoelectronics and photovoltaics. Herein, the chiral Zn‐based organic−inorganic hybrids are discovered: [(R)‐(−)‐2‐methylpiperazine‐1,4‐diium][Zn(H2O)6]•(SO4)2 (RMPZnS2, space group P21) and [(S)‐(+)‐2‐methylpiperazine‐1,4‐diium]2[Zn(H2O)6]•(SO4)3 (SMP2ZnS3, space group P21212). Through experimental and computational investigations, it is found that RMPZnS2 is a ferroelectric with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 43 publications
0
15
0
Order By: Relevance
“…Organic–inorganic hybrid materials have attracted considerable attention because of their flexible structure and remarkable properties, such as photovoltaic, ferroelectric and. piezoelectric, and nonlinear optical (NLO) properties. Among them, layered two-dimensional (2D) organic–inorganic halide perovskites (as an emerging semiconducting materials, they possess a strong quantum confinement effect to achieve high PLQYs and, moreover, photochromism can also be adjusted by halogen) have widespread applications in solar cells, , light emitting diodes (LEDs), and photodetectors. …”
Section: Introductionmentioning
confidence: 99%
“…Organic–inorganic hybrid materials have attracted considerable attention because of their flexible structure and remarkable properties, such as photovoltaic, ferroelectric and. piezoelectric, and nonlinear optical (NLO) properties. Among them, layered two-dimensional (2D) organic–inorganic halide perovskites (as an emerging semiconducting materials, they possess a strong quantum confinement effect to achieve high PLQYs and, moreover, photochromism can also be adjusted by halogen) have widespread applications in solar cells, , light emitting diodes (LEDs), and photodetectors. …”
Section: Introductionmentioning
confidence: 99%
“…31 Another example is that Wu et al synthesized zinc-based chiral hybrid organic−inorganic RMPZnS 2 and SMP 2 ZnS 3 single crystals, in which the RMPZnS 2 crystal is ferroelectric. 32 In addition, Jiao et al also reported a H/F-substituted HOIF (C 4 H 8 NF 2 ) 2 CdCl 4 , in which two different solvents were used to obtain a ferroelectric and a non-ferroelectric. 33 At present, the number of zinc-based ferroelectrics is still relatively small.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Chen et al reported an HOIF [(CH 3 ) 3 NCH 2 F]­ZnCl 3 with a zinc chloride ABX 3 structure, in which the organic molecules were substituted with H/F to optimize ferroelectricity . Another example is that Wu et al synthesized zinc-based chiral hybrid organic–inorganic RMPZnS 2 and SMP 2 ZnS 3 single crystals, in which the RMPZnS 2 crystal is ferroelectric . In addition, Jiao et al also reported a H/F-substituted HOIF (C 4 H 8 NF 2 ) 2 CdCl 4 , in which two different solvents were used to obtain a ferroelectric and a non-ferroelectric .…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain such multifunctional materials, [22][23][24] great efforts have been made to explore the relationship between their inherent structure and potential properties. For example, Wu et al 25 reported chiral Zn-based organicinorganic hybrid RMPZnS 2 and SMP 2 ZnS 3 single crystals with a large polarization value of 9.5 μC cm −2 and luminescence characteristics. In addition, Zhang et al 26 synthesized a temperature-triggered dielectric switch nanocomposite (ODA for short), in which the dielectric switch showed good stability after multiple temperature cycles, indicating that the material is an excellent switchable dielectric material.…”
mentioning
confidence: 99%